Frutos ambíguos do afeto: Um estudo sobre a problematicidade dos personagens André e Ana em lavoura arcaica - Férrer, Jéssica Rodrigues (2016)
This study purposes an analysis of the literary work Lavoura Arcaica (1975), wrote by Raduan Nassar, accentuating the examination of the characters André and Ana. Exploring to describe their individual conflicts, The analysis will use concepts found on The theory of the Novel, by Georg Lukács, principally on his structural irony's conception and problematic hero. Also, a critical use of Lukacsian typology, exposed on the second part of the Hungarian philosopher's work. Furthermore, we notice that the transgressor and the problematic desirability of André and Ana finish in their incest act. Thus, we believe that the incest is the exponent of the incompatibility of the characters André and Ana with external world, also being the trigger element of the tragedy in the book. Contributing with the critical fortune of Raduan Nassar and expanding the debates about the character of the novel are justifiable interests in this present work. We seek to trace an analysis of the protagonist trajectory André to his sister Ana, observing how them can be considered problematic heroes inside the novel configurations.